The Modified Glasgow Prognostic Score Predicts Survival in Gastric Cancer Patients with Normal CEA and CA19-9 - Shun Zhang; Jing-Ze Li; Tao Du; Hai-Qiang Li; Ren-Hao Hu; Chi-Ye Ma; Xi-Mao Cui; Chun Song; Xiao-Hua Jiang (Canadian Journal of Gastroenterology and Hepatology)
Background. Traditionally, serum CEA and CA19-9 levels are good prognostic factors for gastric cancer. Many gastric cancer patients do not have elevated CEA or CA19-9 levels even at a very advanced stage. This study investigates the significance of the modified Glasgow prognostic score (mGPS) for the survival of gastric cancer patients with normal CEA and CA19-9. Methods. We retrospectively examined 488 curatively resected gastric cancer patients with normal preoperative serum levels of CEA and CA19-9 to evaluate the prognostic ability of mGPS for overall survival. The prognostic significance was analyzed by univariate and multivariate analyses. Results. Age, hemoglobin, white cell count, and neutrophils were each significantly correlated with the mGPS. Multivariate analyses showed that tumor location (HR, 0.803; 95% CI, 0.667–0.966; P=0.020), TNM stage (HR, 2.714; 95% CI, 2.250–3.275; P<0.001), and mGPS (HR, 1.042; 95% CI, 1.105–1.772; P=0.023) were significantly associated with overall survival. Significant correlations were found between overall survival and mGPS. The Kaplan–Meier analysis demonstrated significant differences among patients with mGPS of 0, 1, and 2 P<0.001, with the mortality rate being higher for patients with a higher mGPS. Conclusion. The mGPS can predict survival in gastric cancer patients with normal CEA and CA19-9.